Estudo prospectivo e genotipagem do HPV em pacientes com papilomatose laríngea e nasal – São Luís, Maranhão - BRITO, Danielle Salgado de (2019)
Human papillomavirus (HPV) is a non-enveloped virus that infects the cutaneous and mucosal epithelium. Its transmission is mainly sexual, and may also occur by autoinoculation or vertical transmission. Laryngeal (PL) and nasal (PN) papillomatosis are caused by types 6 and 11 of HPV in 90% of cases. In the larynx, the disease tends to have an aggressive clinical course mainly in children and can be fatal due to its high recurrence and tendency to spread through the respiratory tract. The objective of this study was to analyze sociodemographic and clinical data, as well as HPV genotyping found in patients with PL and PN treated at a reference hospital in São Lu-is – Maranhão. This cross-sectional, prospective study was carried out with 12 patients, using fresh samples of papillomatous lesions of the larynx and nasal cavity. Sociodemographic and clinical data were collected from a questionnaire applied directly to the patient, medical and histopathological reports. For analysis of human papillomavirus infection, the DNA was extracted from papilloma samples collected during surgery and submitted to polymerase chain reaction (PCR). Positive samples were submitted to the automated sequencing technique for viral genotyping. The majority of the patients were males (58.33%), brown (91.67%) and residents in the interior of the state (58.33%). About 75% had PL and 25% PN. Vaginal delivery was the most frequent among patients (91.67%). Among the patients with PL, the juvenile type was the most prevalent with 75% of the cases. Among the clinical manifestations characteristic of the LP, it was observed that all patients had dysphonia, 66.67% had dyspnea and 33.33% had dysphagia. The majority (77.78%) presented recurrence of the disease. The presence of HPV was detected in 100% of the cases (larynx and nasal cavity), being type 6 more prevalent. In conclusion, the evaluated population of PL and PN patients was composed mainly of male infected by HPV-6 with dysphonia and a high rate of recurrence of the disease. The clinical knowledge of PL and PN are essential to verify the correct diagnosis of the disease and, consequently, to clarify and guide the family about the surgical removal of papillomas, considering it to be the main treatment since it does not have a definitive cure.